TERRITORIAL PATTERN OF PUBLIC SPACE IN THE KEMBANG JEPUN AREA - Nurahma, Tarisa; Sabrina, Adelia Nur; Shalimar, Raniya Salsabila; Winasih, Sri Suryani Yuprapti (ADBE, 2023)
The Chinatown area is a settlement of the Chinese ethnic group which is closely related to history and is often the oldest area in various cities in Indonesia. The Chinese community is an integral part of urban development and reflects the socio-economic resilience of the community with an ongoing center of economic and cultural activity. As an area that is rooted in tradition and the social order of a particular community, characteristics of the physical and non-physical components of the area are found. This is an identity that indirectly becomes the territorial boundaries of the surrounding environment. Kembang Jepun is a Chinatown area that is the main settlement and trade center for the Chinese community in the city of Surabaya. However, over time, the identity of Kembang Jepun as a Chinese village has been affected by urban development, the emergence of residential and trading areas has made the territorial pattern of public space in the Kembang Jepun area increasingly eroded. The purpose of this research is to identify the pattern of public territories found in the public spaces of the people of Kembang Jepun Village, Surabaya. By using physical observation methods and behavior mapping to find out social phenomena that occur naturally. In supporting the method, observation, interview, and documentation techniques are used which are described in terms of existing conditions. The results of the research are primary and secondary territory coverage areas bordering the fixed, semi-fixed, and non-fixed elements of community behavior to control the territory to create privacy in defending oneself from outside influences.